Educação em saúde e autocuidado como estratégias para controle do Diabetes Mellitus: revisão integrativa fundamentada na teoria de Orem. - Natan Felipe da Rocha Máximo; Jamilly Jacinto Palma; Érica Fernanda Pedro; Josélia Cardoso dos Santos; Jaqueline Soares dos Santos; Andressa Merlo Jaques; Isabella Angeli; Adriene de Freitas Moreno Rodrigues (Revista ft, 2026)
Objective: To analyze the scientific evidence regarding health education developed by nursing professionals in the care of people with Diabetes Mellitus, based on Dorothea Orem's Self-Care Deficit Theory. Method: This integrative literature review was conducted using the Virtual Health Library (BVS), Scientific Electronic Library Online (SciELO), and PubMed/MEDLINE databases. Original articles published between 2016 and 2025, available in full text and related to nursing educational interventions for people with Diabetes Mellitus, were included. After applying the inclusion and exclusion criteria, ten studies were selected for the final sample. Results: The findings demonstrated that educational interventions conducted by nurses contribute to increased knowledge about the disease, improved self-care practices, better treatment adherence, enhanced health literacy, and improved glycemic control. Nursing consultations, educational groups, collective activities, home visits, and telephone follow-up were identified as effective educational strategies. Challenges related to professional qualification and structural limitations of health services were also identified. Conclusion: Health education developed by nursing professionals is an essential strategy for promoting autonomy and selfcare among people with Diabetes Mellitus, contributing to the prevention of complications and improvement of quality of life. Orem's theory proved to be an appropriate theoretical framework to support nursing educational practices in this context.